2022
DOI: 10.18280/rcma.320306
|View full text |Cite
|
Sign up to set email alerts
|

Tribological and Mechanical Performance of Epoxy Reinforced by Fish Scales Powder

Abstract: The study was conducted to use fish scales powder as animal biomass to prepare epoxy composites. Fish scales powder is beneficial in reducing environmental pollutants. The fish scales powder was added to the epoxy matrix for improving the interfacial bonding between the scales and the epoxy matrix. However, a direct method was used to prepare epoxy composites, and samples were cut according to ASTM standards for mechanical and tribological tests. Interfacial interaction between the fish scales powder and epoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…As a result, reinforcements should only be applied up to a certain weight fraction; otherwise, they are pointless. This can be attributed to the agglomeration and increasing porosity with higher reinforcement content, as well as the optimal weight fraction of reinforcement varying amongst composites [10,11]. AA 6061 was mixed with (2.5 to 7.5wt%) of SiC-Al2O3 and (0.5 to 2.5wt%) of rare earth CeO2 by Vipin et al Following the inclusion of cerium oxide, the findings showed improved mechanical characteristics with decreased porosity (rare earth particles).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, reinforcements should only be applied up to a certain weight fraction; otherwise, they are pointless. This can be attributed to the agglomeration and increasing porosity with higher reinforcement content, as well as the optimal weight fraction of reinforcement varying amongst composites [10,11]. AA 6061 was mixed with (2.5 to 7.5wt%) of SiC-Al2O3 and (0.5 to 2.5wt%) of rare earth CeO2 by Vipin et al Following the inclusion of cerium oxide, the findings showed improved mechanical characteristics with decreased porosity (rare earth particles).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 12 shows the presence of SiC and Graphite particles are uniformly distributed. The dendritic structure was equally shaped and shows a uniform distribution, which indicates improvements in strengths up to 6 wt.% after that due to particle agglomeration the strength decreased [25]. The wear rate of Al MMC's and base alloy increased exponentially with increasing load and sliding distance, as shown in Figures 13-15.…”
Section: Percentage Of Elongationmentioning
confidence: 86%
“…To find out the best treatment, the LSD test was carried out as presented in Table 3. The result indicates that the higher the adhesive content, the higher the IB value of the particleboard [33,16]. Among the factors contribute to the IB value of particleboard is adhesive.…”
Section: Internal Bond (Ib)mentioning
confidence: 97%